Vitamin D Insufficiency in Overweight and Obese Children and Adolescents - Zakharova, Irina; Klimov, Leonid; Kuryaninova, Victoria; Nikitina, Irina; Malyavskaya, Svetlana; Dolbnya, Svetlana; Kasyanova, Anna; Atanesyan, Roza; Stoyan, Marina; Todieva, Anastasiya; Kostrova, Galina; Lebedev, Andrey (Frontiers in Endocrinology, 2019)
Excessive body weight and obesity in childhood and adolescence are becoming more and more important unfavourable factors that entail extremely adverse consequences and require close attention of physicians of any specialty. Along with the high prevalence of obesity and metabolic syndrome in paediatric patients, children and adolescents in the majority of countries are diagnosed with vitamin D deficiency. Among the non-calcaemic effects of vitamin D, a significant role is played by its impact on the hormonal regulation of glucose metabolism and the synthesis of adipokines by fat tissue. The review presents literature data indicative of a close pathogenic relationship between vitamin D insufficiency and impaired tissue insulin sensitivity. It demonstrates the role of vitamin D insufficiency in immune reactions resulting in development of subclinical inflammation in fat tissue infiltrated with macrophages and lymphocytes. It also shows the role of adipokines, immune system cells and pro-inflammatory cytokines produced by them in the pathogenesis of obesity, as well as the function of vitamin D as an endocrine and paracrine regulator of the process of inflammation in adipose tissue. The relationships between the principal adipokines (leptin, adiponectin, resistin) are revealed in the presence of normal vitamin D content and in vitamin D deficiency. The carbohydrate and lipid metabolism parameters in overweight children and adolescents with vitamin D insufficiency are analyzed. A high prevalence of vitamin D insufficiency in overweight and obese children and adolescents (increasing along with the severity of obesity) is demonstrated. The review also presents the current recommendations for the correction of vitamin D insufficiency and underlines the need for higher cholecalciferol doses to achieve serum calcifediol targets in overweight and obese children and adolescents.